Critical Micelle Concentration Of Mixed Anionic Znd Zwitterionic Surfactant System In Different Media - Spittcy, Anak Clive Renyang (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Critical Micelle Concentration (CMC) is parameter that commonly used to evaluate and predict the aggregation behavior of surfactant when some particular physiochemical changes occur in solution system. In this experiment, the CMC of the surfactant system of single (ZW3-12 and SDS) in aqueous (phosphate buffer) medium and mixed (SDS+ ZW3-12) surfactant system in different media (aqueous and soil) was determined by using the spectrophotometer method through UV-Vis spectrum of pyrene monomer in specific range of wavelength (263-335 nm) and the data was compared to investigate the significant changes on aggregation behaviour between of both surfactants. Pyrene was added on the surfactant solution to enhance the solubility of surfactant for forming micelle on the aqueous solution. Result show that the CMC the single SDS is high than ZW3-12 surfactant with ZW3-12 give early aggregation while in mixed surfactant system, the CMC was increased with increasing of mole fraction of SDS and the graph pattern of CMC in soil medium show higher measurement than aqueous medium. Based on the data, concluded that the CMC in the certain surfactants are depend on several factor such as their chemical nature in the solution and surfactant, ionic strength and interfacial activity that contribute to alter or promote the interaction forces between surfactant molecule that related to with hydrophilic and hydrophobic section.